A comparison of EFECE systems with tension band wiring for patella fracture fixation in cadavers - Karadeniz, Emre (J Orthop Surg Res, 2020)
BACKGROUND: EFECE systems are newly defined internal fixation systems, which are suitable for patella fracture fixation. The aim of this study was to compare the fixation strength of EFECE Systems with tension band wiring for transverse patellar fracture simulation on fresh frozen cadaver models. METHODS: Quadriceps tendon-patella-patellar tendon (QT-P-PT) complex was prepared from human cadavers. After simulation of a transverse patella fracture, in group 1, 5 patella were fixed with a pair of 1.2 mm EFECE wires and 4 EFECE devices. In group 2, 5 patella were fixed with a pair of 1.2 mm Kirschner wires (K-wire) and a cerclage wire according to the tension band technique. Using a testing device with custom-made jaws, increasing distraction force was applied to these QT-P-PT complexes. Extension of these complexes with the distraction forces was observed. The maximum distraction force and the elongation during maximum force were evaluated. RESULTS: After 5 experiments with the EFECE systems, there was no EFECE wire breakage or EFECE wire-EFECE device catching failure. The median maximum force was 740 N (720-810 N). During maximum distraction force the median extension was 2.5 mm (1.6-2.5 mm). After 5 experiments with the tension band technique, there was no K-wire breakage. The median maximum force was 330 N (240-510 N). During this maximum distraction force the median extension was 3.4 mm (2.2-3.8 mm). CONCLUSIONS: Based on the biomechanical advantages, patella fracture treatment with EFECE systems may constitute a reasonable alternative in the treatment of patella fractures.